Het leven en de lotgevallen van Robinson Crusoe, t. 2 - Defoe, Daniel, 1661?-1731 (Salt Lake City, UT : Project Gutenberg, 2012)
"Het leven en de lotgevallen van Robinson Crusoe, t. 2" by Daniel Defoe is a novel first published in 1719. After being shipwrecked on a remote tropical island, Robinson Crusoe spends 28 years surviving alone near the Venezuelan coast. He builds shelter, grows crops, and raises animals while reading the Bible. His solitude is shattered when cannibals visit the island. Crusoe rescues a prisoner he names Friday, and together they face new arrivals$1 (Bboth threatening and hopeful$1 (Bthat may finally offer escape from his island prison. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Robinson_Crusoe Wikipedia page about this book: https://nl.wikipedia.org/wiki/Robinson_Crusoe
Release date is 2012-11-21
Produced by Anne Dreze, Annemie Arnst & Marc D'Hooghe (Images generously made available by the Hathi Trust)
Keywords: Shipwreck survival -- Fiction; Islands -- Fiction; Crusoe, Robinson (Fictitious character) -- Fiction; Atlantic Ocean -- Fiction; Adventure stories; Castaways -- Fiction